An open-label non-randomized prospective pilot study of the efficacy of Q-switched Nd-YAG laser in management of facial lichen planus pigmentosus. (17th February 2019) - Shah, Dr. Swapnil Deepak; Aurangabadkar, Dr. Sanjeev; Nikam, Dr. Balkrishna
ABSTRACT: Lichen planus pigmentosus (LPP) is a cosmetically disfiguring condition. Many treatment options are available which are effective in halting the progression of the disease. The treatment of persistent pigmentation is still a challenge. We describe the use of Q-switched Nd-YAG laser in 13 patients with stable LPP using a standard protocol. Most of our patients showed complete to near-complete resolution of pigment without much complications.